Herbal Drug Development for Alzheimer’s Disease: A Promising Approach through Computer-Aided Drug Design - Baviskar, Bhushan Arun; Deore, Sharada Laxman; Shende, Bhavana Ashokrao; Kide, Anjali Ashokrao (Pharmacognosy Reviews)
Dementia has arisen as a severe worldwide health concern in recent decades as the world's population ages. The most frequent kind of dementia is Alzheimer's Disease (AD). Despite substantial medication and developmental research, there are just a few FDA-approved medications for Alzheimer's disease. Alternative methods to AD therapies are urgently needed since existing medicines merely give symptomatic alleviation and are usually linked with side effects. A number of medicinal plants have been identified as nootropics, which increase mental and cognitive capabilities by influencing various brain physiological pathways. In silico methodologies, often known as Computer Aided Drug Design (CADD) investigations, are becoming more popular in industry and universities. They include a thorough grasp of molecular interaction from both a qualitative and quantitative standpoint. These approaches create and modify 3D molecular structures, distinct molecular attributes, and compute descriptors then design models, and use other computing drug research tools. The molecular structure of a system may be analyzed to extract useful information and forecast the potential of bioactive chemicals. This review focuses on in silico screening of certain phytochemicals which can be found beneficial in Alzheimer’s disease.
Keywords: Alzheimer’s disease; Alkaloids; Flavonoids; Terpene